Conformational Analysis for 3-Halopropene in Gas Phase using The Complete Basis Set (CBS) Limit Extrapolation Scheme - Badawi, Mohammad Abd Al-Hakim; Ismail , Adham (Latakia University Journal -Basic Sciences Series, 2020)
The potential energy surfaces of the internal rotation of 3-halopropene CH2 = CH- CH2X (X = F, Cl, Br) were determined by the DFT theory (M06-2X) using the Complete Basis Set (CBS) Limit Extrapolation Scheme ccpVXZ; where X = D, T, Q. The optimization geometry of the molecules was obtained using the level of theory M06-2X/6-31g(d). The calculated potential energy curves in this research were compared with experimental and theoretical curves. The Results of this research are well agree with the experimental curves of the internal rotation for X = F, Cl, and the theoretical and experimental curves are not consistent for X = Br. Based on the results of this research, potential barriers and energy (enthalpy) differentials were calculated for the studied 3-halopropene. The relative stability between the cis and gauche conformers differs according to the studied halogen.